2023
DOI: 10.1007/s11274-023-03516-4
|View full text |Cite|
|
Sign up to set email alerts
|

Simulatenous evaluation of composting experiments and metagenome analyses to illuminate the effect of Streptomyces spp. on organic matter degradation

Abstract: Streptomyces spp. were isolated via sampling during thermophilic phase of a compost system. Isolates were subjected to a careful and detailed sets of procedures in order to select best candidates effective on organic matter degradation. This effect, on organic matter degradation was illumanated by evaluation of composting experiments and metagenome analyses in accordance. Results indicated dominanace of strains when added to compost systems. This dominanace was found to be partially due to possible secondary m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
0
0
2
Order By: Relevance
“…The potential of Streptomyces spp in pollution degradation in effluent from paper pulp has been proven through the detection of breakdown products observed after incubation period [297] . Furthermore, a recent study done by Kocak et al [298] found that The introduction of Streptomyces spp. to the compost system resulted in significant changes, including the inhibition of other microbiota members.…”
Section: Streptomyces Impact On Composting Processmentioning
confidence: 99%
“…The potential of Streptomyces spp in pollution degradation in effluent from paper pulp has been proven through the detection of breakdown products observed after incubation period [297] . Furthermore, a recent study done by Kocak et al [298] found that The introduction of Streptomyces spp. to the compost system resulted in significant changes, including the inhibition of other microbiota members.…”
Section: Streptomyces Impact On Composting Processmentioning
confidence: 99%
“…Streptomyces'in organik madde bozulması üzerindeki etkisini aydınlatmak için kompostlama deneyleri gerçekleştirilmiş ve kompost sistemlerine eklenen suşların tüm kompost mikrobiyotasına hâkim olduğu ve bu aşamadaki en önemli faktörün enzim aktivitesi olduğu rapor edilmiştir (Kocak et al 2023). Bostubayeva ve arkadaşları (2023) yaptıkları çalışmada iki Streptomyces türünün kompostlama süreçlerinde iyi bir biyoaktivatör olacağını rapor etmişlerdir.…”
Section: Yakın Zamanda Gerçekleştirilen Kapsamlı Bir çAlışmadaunclassified
“…Yüksek selülaz aktivitesi, kompost olgunlaşmasının hızlandırılmasına yol açan selüloz bozunmasına neden olur. Selülaz enzimleri mikroorganizmaların selüloza ulaşmasını kolaylaştırarak mikrobiyal aktiviteyi ve biyokütle üretimini arttırır (Sun et al 2021, Kocak et al 2023. Ayrıca, selülozun selülaz tarafından enzimatik olarak parçalanması, karbon, azot ve fosfor gibi besinlerin salınmasına katkıda bulunarak bu bileşiklerin bitki tarafından alımını kolaylaştırır (Mazumder et al 2021).…”
Section: Introductionunclassified